1987
DOI: 10.1111/j.1432-1033.1987.tb13480.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII binds to von Willebrand factor via its Mr-80000 light chain

Abstract: The formation of a complex between factor VIII (FVIII) and von Willebrand factor (vWF) was studied using purified radiolabeled human FVIII and purified human vWF. A binding assay was developed in which vWF was coated on microtiter wells. FVIII was shown to bind specifically and reversibly to the immobilized vWF. At a coating of 70 pg vWF/well, binding was half-maximal at a FVIII concentration of 70In order to ascertain which part of FVIII interacted with vWF, eight monoclonal antibodies, directed against FVIII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 28 publications
3
63
0
2
Order By: Relevance
“…We now speculate that the protective effect of von Willebrand factor on activation and inactivation of factor VIIl by factor Xa is caused by its ability to block the phospholipid-dependent binding of factor Xa to factor VIII. von Willebrand factor, which binds to the light chain of factor VIII [29,311, has been shown to compete with phospholipids in binding to factor VIII [32]; we have recently described a similar effect of von Willebrand factor on the inactivation of factor VIII by activated protein C [27], a reaction which is also dependent on phospholipid. Further studies are required to characterize further the mechanism and physiological relevance of the phenomenon described in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We now speculate that the protective effect of von Willebrand factor on activation and inactivation of factor VIIl by factor Xa is caused by its ability to block the phospholipid-dependent binding of factor Xa to factor VIII. von Willebrand factor, which binds to the light chain of factor VIII [29,311, has been shown to compete with phospholipids in binding to factor VIII [32]; we have recently described a similar effect of von Willebrand factor on the inactivation of factor VIII by activated protein C [27], a reaction which is also dependent on phospholipid. Further studies are required to characterize further the mechanism and physiological relevance of the phenomenon described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…1251-factor VIII (I0000 cpm/well) was bound to the immobilized von Willebrand factor for 2 h at 37°C and the wells were washed with 0.3% BSA/O.l% Tween-20. This binding system has been described and characterized before [29]. To study the release of proteolytic products of factor VIII from von Willebrand factor, the wells were incubated at 37°C with factor Xa (10 pg/ml, 200 nM) in a 50 4 1 2 3 Fig.…”
Section: Binding Of Factor VIII To Von Willebrand Factor and Elution mentioning
confidence: 99%
See 1 more Smart Citation
“…When those experiments were performed, the binding of FVIII to VWF was attributed to two FVIII regions: the carboxy-terminal part of the C2 domain and the acidic part of the A3 domain [15][16][17][18]. It was therefore unexpected that Mab-LE2E9, which recognizes an epitope in the C1 domain, could interfere with FVIII binding to VWF.…”
Section: Role Of the C1 Domain In Fviii Binding To Vwfmentioning
confidence: 99%
“…The binding of FVIII to vWF is important for the survival of FVIII as the plasma concentration of FVIII is considerably reduced in the absence of vWF (6)(7)(8). FVIII binds to vWF involving A3 and C2 domains of the light chain (9)(10)(11)(12)(13). It has been shown that the A2, A3, and C2 domains of FVIII are involved in the interaction with LRP (14,15).…”
Section: Introductionmentioning
confidence: 99%